Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Matematika dengan Model Pembelajaran Course Review Horay - Muhammad Rezki Andhika; Mauliza Mauliza (Pedagogi: Jurnal Ilmu Pendidikan, 2022)
This research is motivated by the low motivation to learn in mathematics. The purpose of this study was to determine whether there was a change in students' learning motivation after the application of the Course Review Horay learning model. This study used a pre-experimental approach, which the samples were students of class III MIN 8 West Aceh, totaling 37 students of class III-A. The instruments used are questionnaires, observation guidelines and documentation. Data was collected using a closed questionnaire. While the data analysis was carried out by comparative descriptive analysis with SPSS. The results obtained before the application of the Course Review Horay learning model there were 21 students with low motivation, 13 students with moderate motivation and 3 students with high motivation with an average score of 36.34. After the application of the Course Review Horay learning model, there were no students with low motivation, 3 students with moderate motivation and 34 students with high motivation with an average score of 68.8. It can be concluded that there is a change in learning motivation after the application of the Course Review Horay learning model